Cellular internalization kinetics of (luciferin-)cell-penetrating peptide conjugates. - Eiríksdóttir, E; Mäger, I; Lehto, T; Andaloussi, S; Langel, U (2010)
Cell-penetrating peptides (CPPs) belong to a class of delivery vectors that have been extensively used for the cellular delivery of various, otherwise impermeable, macromolecules. However, results on the cellular internalization efficacy of CPPs obtained from various laboratories are sometimes challenging to compare because of differences in the experimental setups. Here, for the first time, the cellular uptake kinetics of eight well-established CPPs is compared in HeLa pLuc 705 cells using a recently published releasable luciferin assay. Using this assay, the kinetic behavior of cytosolic entry of these luciferin-CPP conjugates are registered in real time. Our data reveal that the uptake rate of CPPs reaches its maximum either in seconds or in tens of minutes, depending on the CPP used. Tat and higher concentrations of MAP and TP10 display fast internalization profiles that resemble the kinetic profile of membrane-permeable free luciferin. The uptake of the other peptides, pVec, penetratin, M918, and EB1, is much slower and is consistent with the reported observations of endocytosis being the predominant internalization mechanism. Additionally, to some extent, the latter CPPs can be clustered into subgroups which are based on time points when the most pronounced uptake rates are observed. This may indicate once more involvement of various (concentration dependent) mechanisms in the uptake of CPPs. In summary, the variances in the internalization profiles for the CPPs demonstrate the importance of measuring kinetics instead of only relying on simple end-point studies, and with the luciferin-CPP assay, more lucid information can be retrieved when studying the internalization mechanisms of CPPs.